Analysis of early results of edoxaban and warfarin in the treatment of deep vein thrombosis - Abdullah Guner; Volkan Burak Taban; Muhammet Talha Ceran; Yuksel Dereli (Turkish Journal of Vascular Surgery)
Aim: Deep Vein Thrombosis (DVT) is an acute onset disease. Warfarin and new oral anticoagulants (NOAC) can be used for treatment. Edoxaban is one of the NOACs that acts directly as a ‘Factor Xa inhibitor'. The aim of our study was to investigate early treatment complications and efficacy in patients treated with warfarin and edoxaban. Material and Methods: The results of a total of 100 patients who started drug treatment for DVT between September 2018 and March 2020 were retrospectively analysed. The patients included in the study were divided into two groups according to the type of anticoagulant used [Warfarin (n=50), Edoxaban (n=50)]. Patients' routine examinations and colour Doppler ultrasound (CDUSG) results at baseline and 1-month follow-up were compared with their bleeding status. Results: Clinical status and CDUSG revealed acute DVT in 57 patients, subacute DVT in 32 patients, and chronic DVT in 11 patients. The recanalisation rate at 1 month was higher with edoxaban (80%) and lower with warfarin (62%) and this difference was statistically significant (p=0.008). The most common complication during follow-up was minor bleeding, which occurred in 24% and 18% of patients using Warfarin and Edoxaban, respectively. There was no mortality due to minor, major or cerebrovascular events in any of the patients. Conclusion: In our study, we evaluated the early results of anticoagulant therapy in patients with DVT and found faster recanalization and fewer complications in the NOAC group in agreement with the literature. Further randomised, advanced and large-scale studies are needed to evaluate the efficacy of the drugs. [Turk J Vasc Surg 2024; 33(3.000): 127-31]